Human Appeasing Pheromone (HAP) influence on behavior and psychopathological residual symptoms of patients with complex psychiatric disorders. Issue 4 (23rd February 2018) - Piccinni, Armando; Veltri, Antonello; Marazziti, Donatella; Mucci, Federico; Cozzi, Alessandro; Pageat, Patrick
Key Clinical Message: This article is a case‐report series showing the effectiveness of a three‐month exposure to a synthetic analogue of Human Appeasing Pheromone as add‐on strategy to psychopharmacological treatment on behavioral and residual symptoms of three patients suffering from severe psychiatric disorders with complex clinical pictures. Abstract : This article is a case‐report series showing the effectiveness of a three‐month exposure to a synthetic analogue of human‐appeasing pheromones as add‐on strategy to psychopharmacological treatment on behavioral and residual symptoms of three patients suffering from severe psychiatric disorders with complex clinical pictures or residual invalidating symptoms.